Tourist Places at Kanyakumari District in Tamilnadu (Journal of Basic and Applied Research in Biomedicine, 2022)
Tourism is a fast growing industry which has vast and inexhaustible potentials to enhance national income, foreign exchange reserves and opportunities of employment to the growing millions or the countries. The size and economic significance of travel and tourism have attracted the attention of many countries in actively promoting tourism as a way to stimulate their economies. The world tourism organization has recognized the potential of tourism sector for the purpose of poverty alleviation by increased job creation; consequently, many developing countries are improving their tourism planning and developments approaches. The objective of this research article is to study the tourist places in kanyakumari district. .